The (home) bias of European central bankers: New evidence based on speeches - Hamza Bennani; Matthias Neuenkirch (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
Speeches are an important vehicle for central bankers to convey individual views on the preferred policy stance. In this paper, we employ an automated text linguistic approach to create an indicator that measures the tone of the 1,618 speeches delivered by members of the Governing Council (GC) during the period 1999M1..2014M4. We then relate this variable to euro-area and national macroe- conomic forecasts. Our key findings are as follows. First, inflation and growth expectations have a positive and significant impact on the hawkishness of a speech. Second, the voiced preferences of national central bankers largely coincide with the level of independence their banks had at the time of the Maastricht Treaty. Third, country-specific macroeconomic conditions matter for speeches delivered inside the central banker's home country but not for those made abroad. Fourth, differences in central banker preferences are the key source of variation in their speeches before the financial crisis, whereas divergent national economic conditions are the main factor in the second part of the sample.
Keywords: E52; E58; 330; Central Bank Communication; European Central Bank; Governing Council; Monetary Policy; National Interests; Speeches